Design and Build a Smart Electrical Socket Using Iot Based Arduino Uno Microcontroller - Ayu Latifah; Reksya Adi Nugeraha (Universitas Sebelas Maret (UNS), 2024)
Technological developments make it possible to integrate home electrical devices with control via smartphone. One important device is the socket, which many still use conventional models with weaknesses such as the risk of burning if there is excessive current and short circuits due to being stored in damp places. This research aims to design a smart electrical socket that utilizes Internet of Things technology using the Arduino Uno microcontroller. This socket allows users to control electrical sockets and monitor the temperature and humidity around the electrical socket via a smartphone application remotely while connected to the internet. This research uses a prototyping method, which allows gradual development and testing to achieve the desired results. The research results show that the designed system has stable performance with an average measurement delay of 5-22 ms. With the integration of IoT in this electrical socket, users can more easily manage electrical devices and monitor temperature conditions around the electrical socket, which not only adds comfort but also increases the security aspect.